The Protestant Settlers of Israel: Missionaries, Millenarians, and the African Hebrew Israelites - Yudin, Joseph B. (Lexington Books, 2023)
When conjuring an image of “settlers” in the Holy Land, one hardly envisions vast numbers of European and North American Evangelical Protestants. Yet this is precisely the picture set forth in this book. The region has witnessed settlement, conquest, destruction, and resettlement from time immemorial. But the story of Protestants settling in the Land and staking their own claim, while missionizing among the population, has yet to be told in its fullness. The Protestant Settlers of Israel tells that tale, including a discussion of the present-day whereabouts of some 100,000 Protestant individuals living in the State of Israel, with a steady rate of expansion and growth in some circles.